2020
DOI: 10.21009/1.06106
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Thermodynamics Law Experiment Media Based on IoT: Laboratory Activities Through Science Problem Solving for Gifted Young Scientists

Abstract: In this research, thermodynamics law experiment media based on IoT was developed and tested. The purpose was to assess the effectiveness of the IoT-based thermodynamic law experiment media through a problem-based learning approach and laboratory activities using science problem solving for talented young scientists. This research was conducted at SMA 2 Batang. This study using the ADDIE approach model. The development steps are: (1) analyzing curriculum requirements and demands in 2013, (2) designing and manuf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
0
2
0
3
Order By: Relevance
“…Pengembangan media bahan ajar seperti e-modul [10], aplikasi android [11], blended learning [12], dan eksperimen [13] menggunakan model pembelajaran 4D Thiagarajan dan ADDIE. Tetapi pada penelitian ini langkah pengembangan yang dilakukan ini diadaptasi dari Boimau (2020) [14].…”
Section: Metodologiunclassified
“…Pengembangan media bahan ajar seperti e-modul [10], aplikasi android [11], blended learning [12], dan eksperimen [13] menggunakan model pembelajaran 4D Thiagarajan dan ADDIE. Tetapi pada penelitian ini langkah pengembangan yang dilakukan ini diadaptasi dari Boimau (2020) [14].…”
Section: Metodologiunclassified
“…The above study results reveal that the role of the practicum is significant in science learning. Rustaman (2010) suggests four reasons for the importance of practicum activities, namely: (1) it can generate learning motivation, (2) it can develop science process skills (Saputra et al 2021)), (3) become a vehicle for learning with a scientific approach (Liana et al 2020), and (4) strengthen students' understanding through discovery (Haryadi & Pujiasturi 2019). Kohnle et al (2012) revealed that students could understand the concepts and processes with experimental activities.…”
Section: Introductionmentioning
confidence: 99%
“…Physics practicum activities in the laboratory are absolutely carried out as a process of forming student competencies that aim to improve the process of understanding physics concepts. Practical activities are able to train students' basic research skills such as skills in using measuring instruments, skills in choosing appropriate measurement data collection methods, skills in processing obtained measurement data, skills in analyzing data from practicum results, skills in drawing conclusions from practicum results, and skills in communicating practical results [12][13][14].…”
Section: Introductionmentioning
confidence: 99%